Antioxidants deficiency: a sensitive indicator of cardiometabolic risk in chronic renal failure? - Rai, Pooja S.K.; Kamath, Sangita; Bakshi, Amruta A.; Deokar, Smita A.; Rai, Anita B. (International Journal of Research in Medical Sciences, 2017)
Background: Antioxidant depletion occurring in chronic renal failure patients is an important cause of associated morbidity & mortality, which in turn imposes a great socioeconomic burden of health care. Early diagnosis & targeted management of this preventable deficiency may have a positive impact on the management of co morbidities associated with chronic renal failure. Aims & Objectives: To evaluate the status of antioxidants as an early indicator of cardiometabolic risk in chronic renal failure patients. Settings & Design: This was a randomised case Control study including 10 controls of either sex with normal renal function between age group 20-60 years and 15 patients of chronic renal failure on dialysis between the age group of 16 - 60 years. Methods: 12 hour fasting venous blood samples were collected from all the participants and were assayed for various antioxidants. Statistical analysis: Results were analyzed by unpaired t test, p value was determined & Correlation coefficient was calculated amongst various parameters. Results: In the present study, significantly low levels of vitamin C ( Cases: 0.367 ± 0.13 mg/dl controls: 1.324 ± 0.61 mg/dl; p < 0.01) & vitamin E (cases: 0.235 ± 0.102 mg/dl, controls (0.854 ± 0.28 mg/dl; p < 0.01) were observed in chronic renal failure patients as compared to controls. Conclusion: Diminished levels of Vitamin C & E in our study may be an indicator of increased oxidative stress which can be a responsible factor for increased incidence of cardiovascular complications. Supplementing these patients with recommended dosage of these vitamins may provide an essential tool to reduce the burden of suffering.